PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Yuliana; Fatkhiyani, Kiki; Setiawardani, Wawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low learning outcomes of grade IV students of SD 2 Majasari in the 2024/2025 academic year in mathematics learning and the limitations of teachers who only use lecture and discussion models. This study aims to determine the application of problem solving learning models to improve students mathematics learning outcomes. To find out the improvement of students mathematics learning outcomes. The research used is classroom action research (PTK) design Kemmis & Mc Taggart in two cycles that go through four stages, namely planning, implementation, observation, and reflection. The subjects in this study were grade IV students with a total 29 students. The data collection techniques used were interviews, observations and written test. The results of this study show that the results of observations on the application of the problem solving learning model in cycle I obtained an average value of 3.1 with a percentage of 77.5% in the good category and increased in cycle II to 87.5% with an average value of 3.5 and included in the very good category. Learning outcomes obtained by students in cycle I with an average value of 60.2 with a percentage 44.8% increased to 79.7 with a percentage of 86.3% in cycle II. Therefore, it can be concluded that using the problem solving leaarning model can improve students mathematics learning in grade IV of SDN 2 Majasari.